MYOCARDIAL FLOW RESERVE MEASUREMENT USING CADMIUM ZINC-TELLURIDE SINGLE PHOTON EMISSION COMPUTED TOMOGRAPHY MYOCARDIAL PERFUSION IMAGING AND RELATION TO ANGIOGRAPHIC CORONARY ARTERY DISEASE - ASLAM, S; ASLAM, U; AHMED, K; ASLAM, S; KALEEM, M; ASLAM, S (Biological and Clinical Sciences Research Journal, 2024)
The addition of Myocardial flow reserve (MFR) to Single Photon Emission Computed Tomography (SPECT) Myocardial Perfusion Imaging (MPI) by using Cadmium Zinc Telluride (CZT) camera for screening of CAD may improve high-risk patient identification and diagnostic performance. Objective: This study aimed to assess the severity of coronary artery disease using MFR by SPECT MPI and comparing it with angiography finding. Methods: It was a cross-sectional study which was carried out in Armed Forces institute of cardiology and National Institute of Heart Diseases, Rawalpindi from June to Oct 2024. The myocardial flow reserve was calculated using Cadmium Zinc Telluride with 99mTc-sestamibi as radiotracer using SPECT MPI. Disease severity was also assessed using coronary angiography. Chi-square and Fischer exact test was applied for cross-tabulation. Kappa statistics was used to determine the level of agreement between the procedures. P-value less than 0.05 was taken as statistically significant. Results: The 100 patients with mean age of 64.90 + 3.60 years. The mean myocardial blood flow at rest is 1.06 + 0.18 mL/g/min, and at stress is 2.42 + 0.74 mL/g/min. The Myocardial flow reserve mean was 2.23 + 0.52 mL/g/min across sample of study. There is no association between CAD severity determined by SPECT MPI and demographic factors (p > 0.05). Coronary artery disease severity determined by Myocardial flow reserve (MFR) using SPECT MPI and angiography showed statistical significance with p-value of <0.001 and strong agreement with kappa value of 0.784, suggesting MPI SPECT a valuable tool for determining coronary artery disease severity. Conclusion: Cadmium Zinc Telluride gamma camera in SPECT MPI is a user-friendly, non-invasive and low-dose dynamic modality which provides a role of effective indicator of CAD. Myocardial reserve flow played significant role in determination of coronary artery disease severity, suggesting lower the mean myocardial reserve flow the higher the severity of the coronary artery disease. The association between them is also independent of the patient demographics, traditional risk factors and cardiovascular health of the patients, which make SPECT MPI as an independent alternative viable option for diagnosis of CAD.